2020
DOI: 10.1155/2020/9379128
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lifestyle Factors in Controlling Blood Pressure among Hypertensive Patients in Two Health Facilities in Urban Ghana: A Cross-Sectional Study

Abstract: Introduction. Despite efforts to combat hypertension by pharmacotherapy, hypertension control rates remain low. Lifestyle modifications of individuals diagnosed with hypertension have prospects for the prevention and control of hypertension. This study assessed the effect of modifiable lifestyle factors on blood pressure control among adults in urban Accra. Methods. In this cross-sectional study, 360 diagnosed hypertensive patients who were ≥18 years old, selected from two secondary-level referral hospitals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…On the contrary, good practices had been documented from the study conducted in eastern Ethiopia [ 58 ], wherefrom the total of 200 participants around 50% had a good practice on lifestyle modification recommended for hypertension management. Additionally, a prior study from Ghana concluded that the practices of modifying lifestyle factors (increased physical activity, abstaining from alcohol and smoking, and increased intake of fruits and vegetables) in the study subjects are good [ 59 ]. But, an Iranian recent study reported poor adherence and practice to modifiable lifestyle, which is significantly higher in newly diagnosed patients (30.52%) than those who were previously on antihypertensive medication (27.14%) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, good practices had been documented from the study conducted in eastern Ethiopia [ 58 ], wherefrom the total of 200 participants around 50% had a good practice on lifestyle modification recommended for hypertension management. Additionally, a prior study from Ghana concluded that the practices of modifying lifestyle factors (increased physical activity, abstaining from alcohol and smoking, and increased intake of fruits and vegetables) in the study subjects are good [ 59 ]. But, an Iranian recent study reported poor adherence and practice to modifiable lifestyle, which is significantly higher in newly diagnosed patients (30.52%) than those who were previously on antihypertensive medication (27.14%) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, smoking and kidney conditions were required in [ 27 ]; family history, history of hyperlipidemia, and coronary artery bypass graft in [ 29 ]; and diabetes data in [ 26 , 27 , 29 ]. Yet, self-reported diabetes and other medical history conditions are not reliable [ 36 ], and the lifestyle parameters reporting are subjective [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the most recent and relevant research mentioned above, it could be concluded that the use of anthropometric indices together with sociodemographic and lifestyle parameters is beneficial as an initial screening for hypertension. As self-reported diabetes and hypertension are not reliable [ 36 ] and the lifestyle parameters reporting are subjective [ 37 ], in our work, only simple anthropometric measurements together with sociodemographic data are used as the features to predict cases of hypertension. We want to look into how basic anthropometric measurements combined with sociodemographic data may be used to predict hypertension in adolescents and which variables contribute to predicting hypertension.…”
Section: Related Workmentioning
confidence: 99%
“…To monitor and manage hypertensive patients in the best way possible, a comprehensive intervention is needed 60,61 ; this is dependent on many interconnected factors relating to the patient and the healthcare provider as well as how care is provided 62,63 . Previous studies by Modey Amoah et al., 59 show that BP control in patients taking antihypertensive medication is related to modifiable parameters such as duration of physical activity, alcohol consumption, and diet composition.…”
Section: Barriers To Blood Pressure Control Among Hypertensive Indivi...mentioning
confidence: 99%